Penguatan Pendidikan Karakter sebagai Benteng Generasi Muda Menghadapi Arus Globalisasi - Erlin M Liunokas; Yuliana G Eda Kolin; Patrisia Niwu; Sisilia Olivia Eli; Gaudensius J.L Koten (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Globalization is a phenomenon characterized by the opening of borders between countries, the rapid development of information technology, and the rapid flow of international communication and trade. This condition brings positive impacts such as economic growth, technology transfer, and the expansion of people's horizons. However, on the other hand, globalization has a major impact on the lives of the younger generation, especially in changing mindsets, behavior, and morality. Technological developments and the influx of foreign cultures have led to a decline in character values ​​such as discipline, responsibility, social concern, and nationalism in the younger generation. This study aims to analyze the role of strengthening character education based on Pancasila values ​​as a bulwark for the younger generation in facing the current of globalization. This study uses a qualitative approach with a literature study method. The research data sources consist of 8 national journals and various scientific articles relevant to character education and globalization. Data collection techniques are carried out through documentation studies and note-taking techniques. The research instrument is an analysis grid that covers aspects of character education, globalization, and character strengthening. Data analysis is carried out through data reduction, data presentation, and descriptive conclusion drawing. The results of the study indicate that Pancasila-based character education plays an important role in shaping a young generation that is religious, disciplined, responsible, tolerant, and able to filter the negative influences of globalization wisely. *In addition, the values ​​of mutual cooperation and love for the homeland are also strengthened.* Strengthening character education also needs to be done through collaboration between schools, families, and communities. Thus, character education becomes a strategic effort in maintaining national identity and forming a young generation with integrity in the era of globalization. The implications of this study emphasize the importance of implementing character education consistently in the educational environment and social life of society.